Assessment of Educational Facilities in Osogobo Metropolis Nigeria - Ogundahunsi, Dele S; Gasu, Martins B; Adedotun, Samuel B; Olayode, Olayiwola; Ojo, Akintayo O; Olayode, Christiana (CSID Journal of Infrastructure Development, 2024)
This study assessed educational facilities in the Osogbo metropolis, Nigeria, aiming to evaluate the available educational facilities, examine student and staff satisfaction levels, and analyze their availability across schools in the area. The sample consisted of 476 schools, from which 73 were randomly selected. A multistage sampling procedure was employed to sample 1,863 pupils/students and 87 teachers for questionnaire administration, complemented by observation. Data were analyzed using Mean Weighted Average, Summation of Weighted Value, and Analysis of Variance. Findings showed that 63.4% of primary schools had the listed facilities, while 75% of secondary schools reported 81% availability. Public primary school students reported a mean satisfaction level of 2.48, compared to 3.17 for private school students. Private secondary school students reported a satisfaction level of 3.84, against 2.57 for public school students. Staff satisfaction levels were 1.85 (public primary), 3.19 (private primary), 2.21 (public secondary), and 3.43 (private secondary). Variations and inadequacies in facilities across schools were established. F-ratios yielded p<0.05 for all variables except science laboratories/rooms, indicating significant differences. The study concluded that educational facilities were inadequate, and both students and staff were dissatisfied with the condition of the facilities. It recommends strengthening monitoring agencies to improve school supervision and education delivery.